(untitled) (Research, Society and Development, 2022)
Objective: To verify the most used nursing diagnoses regarding Mechanical Ventilation in Intensive Care Units. Method: Integrative literature review, with 11 files selected between the years 2016 to 2021 in the SciELO, BDENF, LILACS and MEDLINE databases. Results: In the studies in question, the following diagnoses were identified: Risk of Infection, Dysfunctional response to ventilator weaning, Risk of Acute Confusion/Acute Confusion, Hospital Infection, Risk of Dry Eye, Risk of Infection, Pain, Ineffective breathing pattern and impaired spontaneous ventilation, in addition to mentioning keratopathy that is not considered a nursing diagnosis, but its inclusion is due to the importance that nurses have in its detection. Conclusion: Knowing about Nursing Diagnoses and associating them with problems related to mechanical ventilation, in addition to being part of the Nursing Process, is an essential step for nurses to become able to offer technical, comprehensive, resolute and systematized assistance to their patients.